Kultus Kiai: Sketsa Tradisi Pesantren - M. Syamsul Huda (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The study on Kiai is a crucial and interesting discussion among the Indonesian Muslim community. This article tries to find the roots of the problem on the emergence of cult tradition towards Kiai, mainly in the pesantren community. The study uses the field observation method, in-depth interview, and interpretation of the results. The research formulates cult tradition towards Kiai within the historical study, model and method of cult transformation, power and kiai’s authority, and a cult's roots among santris’ community. The study finds that cult tradition towards Kiai has emerged from Kiai’s personal power due to his knowledge charisma and his personality as well as institutional charisma as a result of intense and continuous sociological relationships with other institutions.